Vergel de perfectísimas flores. Las dominicas valencianas de Carcaixent según fray José Agramunt. - CALLADO ESTELA, EMILIO (Scripta, 2016)
In this present work, we aim to recover one of the forgotten dominican convents from Valencia. More speciically, the convent of the Corpus Christi located in Carcaixent, on the banks of the River Xúquer. This late Baroque convent was built in 1654. By the eighteenth century, one of his confessors had already made clear its historical interest. We are referring to fray José Agramunt, the author of the unpublished work, Parayso de Dios: Idea del Religiosíssimo Monasterio de Señoras Dominicas de la Real Villa de Carcaxente, analysis in the following pages the life and literal works of the aforementioned religious.